Sexual Dysfunction among Male Veterans Returning from Iraq and Afghanistan: Prevalence and Correlates. (22nd October 2012) - Hosain, G.M. Monawar; Latini, David M.; Kauth, Michael; Goltz, Heather Honoré; Helmer, Drew A.
ABSTRACT Introduction. Sexual dysfunction (SD) is not well described in the Iraq/Afghanistan veteran population despite high prevalence of multiple risk factors for this issue. Aim. To estimate the prevalence and examine the association of various sociodemographic, mental health, comorbid conditions and life style factors with sexual dysfunction in Iraq/Afghanistan veterans. Methods. This exploratory cross‐sectional study was conducted using data from the VA administrative database. A total of 4, 755 Iraq/Afghanistan veterans were identified who sought treatment from the Michael E. DeBakey Veterans Affairs Medical Center inpatient and outpatient clinic between September 2007 and August 2009. Main Outcome Measures. Sexual dysfunction was determined by ICD9‐CM codes related to sexual health issues and/or by specific medications, primarily phosphodiesterase‐5 inhibitors (PDE5i), prescribed for erectile dysfunction. Results. The overall prevalence of sexual dysfunction was 5.5% (N = 265). By age category, it was 3.6% (N = 145) for Iraq/Afghanistan veterans aged 18–40 years and 15.7% (N = 120) for Iraq/Afghanistan veterans aged > 40 years, respectively. A multivariate logistic‐regression model revealed that annual income, marital status, post‐traumatic stress disorder, and hypertension were significant risk factors of SD (all P < 0.05) among younger Iraq/Afghanistan veterans, whereas among the older Iraq/Afghanistan veterans, being African American and having PTSD and hypertension were significant risk factors of SD (all P < 0.05). There was marked discrepancy between documented erectile dysfunction and prescription of a PDE5i. Conclusions. These data demonstrate that a significant proportion of Iraq/Afghanistan veterans have SD and that the risk factors differ between younger and older veterans. Our findings also suggest that SD is likely under‐coded. To better identify the scope of the problem, systematic screening for sexual dysfunction may be appropriate perhaps as part of an initial post‐deployment health evaluation. Hosain GMM, Latini DM, Kauth M, Goltz HH, and Helmer DA. Sexual dysfunction among male veterans returning from Iraq and Afghanistan: Prevalence and correlates. J Sex Med **;**:**–**.